MENGINGKATKAN AKTIVITAS SISWA DALAM PEMBELAJARAN KETERAMPILAN MENGHIAS SULAMAN BENANG EMAS MEMALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE SMPN 1 KECAMATAN PAYAKUMBUH - Desma, Desma; Zahri, Wildati; Ernawati, Ernawati (Journal of Home Economics and Tourism, 2012)
The shortage of activity in making gold yarn embroidery to furnish Carano lid caused by the strategy and learning model which was implemented by the teacher in previous learning session was not suitable and reuslted in the lack of the students activity. One of an effort which can be used to improve that condition is that to used cooperative learning method in the type of think-pair share with some indicators such as; visual activities, drawing activties, motor activities in order to create the students learning activities increase and be better. The research hypotesis is that, the model of cooperative learning type think- pair-share could improve the students activity to ability in furnishing carano lid with gold yarn ebroidery.This research is class action research which consists of two phases and each phase consists of three times meeting and each meeting was 3X 45 minutes. The sample of the research is the students of VII-5 SMP N 1 Payakumbuh Subdistrict in academic year 2011 and 2012, Lima Puluh Kota Regency consisted of 26 Based on the survey toward the students’ activity , it was concluded that through cooperative learning model type think-pair-share could improved the activityin making gold yarn embroidery for Carano Lid in handicraft learning of SMP N.1 Kec. Payakumbuh subdistrict.